2017
DOI: 10.1111/ejn.13553
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB signalling is involved in immune‐modulation, but not basal functioning, of the mouse suprachiasmatic circadian clock

Abstract: Circadian rhythms are recurring near-24 hour patterns driven by an endogenous circadian timekeeping system. The master pacemaker in this system is the hypothalamic suprachiasmatic nucleus (SCN). Recently interest has been drawn to how the SCN clock responds to immune system stimulation. A major signalling component in the immune system is nuclear factor (NF)-κB. In the present study we examined the role of NF-κB in SCN function. Whilst serum shocked fibroblasts showed rhythmic nuclear localisation of p65 and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Moreover, the NF‐κB component also regulates neuroimmune responses. NF‐κB signaling is vital in circadian timing of peripheral cells, which indicates that NF‐κB plays a role in regulating clock processes of CNS and participates in the communication of the brain‐gut axis . This reaction of microbial rhythms stimulates the immune system provides high evidence to support the view that the interaction between melatonin and microbial signaling acts as a prominent role in maintaining the stability of GI function by regulating the circadian system of the host …”
Section: Melatonin Signaling Modulates the Intestinal Immune Functionmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, the NF‐κB component also regulates neuroimmune responses. NF‐κB signaling is vital in circadian timing of peripheral cells, which indicates that NF‐κB plays a role in regulating clock processes of CNS and participates in the communication of the brain‐gut axis . This reaction of microbial rhythms stimulates the immune system provides high evidence to support the view that the interaction between melatonin and microbial signaling acts as a prominent role in maintaining the stability of GI function by regulating the circadian system of the host …”
Section: Melatonin Signaling Modulates the Intestinal Immune Functionmentioning
confidence: 89%
“…Changes in antioxidative capacity may be another means by which melatonin affects B cells. In the immune system, nitric oxide (NO) is an important inhibitory factor for human lymphocyte proliferation . Melatonin inhibits inducible nitric oxide synthase (iNOS) activity and LPS‐induced NO production in wild‐type mice .…”
Section: Activation and Proliferation Of Intestinal Mucosal Immune Cementioning
confidence: 99%
See 1 more Smart Citation
“…To obtain circadian parameters including phase, period length, rhythm amplitude, and damping rate, the LumiCycle Analysis program (Actimetrics) and Actogram J software was used. Luminometry data was detrended and smoothed with a rolling 3 h average as previously described [29,30]. Circadian parameters were derived from cosinor analysis and period was determined from Lomb-Scargle periodograms analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies have indicated that the molecular clock has an important role in almost all metabolic processes in organisms. Furthermore, disruptions to the circadian rhythm may lead to cardiovascular diseases ( 13 ), type 2 diabetes ( 14 ) and immune system diseases ( 15 ).…”
Section: Biological Characteristics Of the Circadian Rhythmmentioning
confidence: 99%